Photocyclization synthesis of phenanthridine and its derivatives under direct dehydrogenation conditions. (2nd February 2021) - Zhu, Wen-Qing; Zhang, Jin; Fan, Pan; Shi, Lan-Ting; Li, Hong; Yang, Min-Ge; Li, Yang
Graphical abstract: Highlights: No need for transition metal catalyst, environmentally friendly and efficient method. The by-product of the reaction is hydrogen. Good selectivity and yield, 8 new phenanthridines are synthesized. Abstract: A new method for synthesizing phenanthridines by photocyclization has been established. This method does not require inert gas protection, does not require transition metal catalysts and is environmentally friendly, efficient and convenient. It is proposed to use ( E )-N, 1-diphenylformimines as substrates to synthesize phenanthridine and its derivatives by ultraviolet light, which provides a new synthesis route for further research on the synthesis of phenanthridines by photocyclization. Eight new phenanthridine compounds were synthesized. The confirmation of their structures provides a material basis for further study of their properties and tapping of their potential for applications. The establishment of this method further broadens the synthetic pathways of phenanthridine compounds.